Aesthetic manifestation and characteristics of creative ceramic culture products by college students in Jingdezhen / DuYue and Fauzi Naeim - DuYue, DuYue; Naeim, Fauzi (Faculty of Art and Design, 2023)
The development of ceramic art in Jingdezhen has a cultural heritage of nearly a thousand years, with unique products and rich categories, which have a profound impact on the development of ceramic culture throughout the country and even the world. The article is based on the Jingdezhen ceramic cultural and creative market as the research basis, and demonstrates and analyzes the aesthetic expression and characteristics of ceramic cultural and creative products of college students in the Jingdezhen ceramic cultural and creative market. And on this basis, reveal the unique aesthetic significance reflected by Jingdezhen ceramic cultural creative products in the modern social and cultural context, and further expand the artistic expression language and aesthetic perspective of Jingdezhen ceramic creative products.